2009
DOI: 10.1016/j.compstruct.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cutout shape and reinforcement design for composite C-section beams under shear load

Abstract: This paper reports a study of the performance of two forms of cutout and various edge reinforcements in a composite C-section beam under static shear load. Firstly, cutout shape effect on stress concentration was studied. This was followed by a comparative study of a range of reinforcement doublers, which were 20 mm wide rings made of a steel alloy or composite laminate, or by a novel fibre tow placement technique. The comparisons are made in terms of the stress and strain reductions at a hot spot at the cutou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Similarly plane windows are rectangular in shape with chamfer at the corners [1]. In plane structures, definite shapes are found as access ports for electrical and mechanical systems or for the reduction of weight [2]. Practically round cutouts are favored due to its simple geometry but there are various designs which offer more advantages over the circular shape.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly plane windows are rectangular in shape with chamfer at the corners [1]. In plane structures, definite shapes are found as access ports for electrical and mechanical systems or for the reduction of weight [2]. Practically round cutouts are favored due to its simple geometry but there are various designs which offer more advantages over the circular shape.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the plate thickness, straight-shank radius, countersunk angle, countersunk depth, plate width, and the laminate ply angles on the SCF were also investigated. The cutout shape effect on stress concentrations of composite C-section beams was studied by Guo et al., 13 which demonstrated that the cutout induced stress concentration can be reduced significantly by appropriate cutout shape and edge reinforcements. Different patch shapes have been applied to the repair of composite panels recently.…”
Section: Introductionmentioning
confidence: 99%
“…Various cutout edge reinforcements were investigated to reduce stress concentration and increase buckling strength [8]. This result was further investigated for the C-section beam in a previous study [9] and relevant to this current research.…”
Section: Introductionmentioning
confidence: 99%